Rancang Bangun Aplikasi Enkripsi Citra Berdasarkan Operasi Rotasi - Wahyudi, Bagus Prasetyo; Rizqiwati, Diah; Akbi, Denar Regata (Jurnal Repositor, 2024)
Cryptography is a discipline that uses mathematical equations when doing the decryption process until encryption. This technique uses to convert the initial message into the form of certain codes, in this study using the rotation method, the rotation method itself is the algorithm to rotate the image on its axis in part of the image. Aiming that information stored and sent to the recipient can’t be read or not easily understood by a third party or parties that are not eligible, advantages of the research made is the speed of fast application process and the decline in file size and not easy manual decryption With other tools, the result of encryption application encoding the occurrence of file size that occurs after the decryption process and encryption when compared with the initial size of the image file, and there is no decrease in the size of the file on BMP extension, the speed of encryption time to the file and the pixel size in the image file extension BMP And PNG on 2000x2000 pixel size has the best speed improvement that is equal to 0.12x faster, and change the histogram in the initial image with the result of encryption. This research is built using Python 3.4 programming language, and coupled with Library PIL-pillow, Library Time.